6-Sulfatoxymelatonin predicts treatment response to fluoxetine in major depressive disorder. (December 2019) - Jury Freitas, Juliana; Bertuol Xavier, Nicóli; Comiran Tonon, André; Carissimi, Alicia; Timm Pizutti, Leandro; Vieira Ilgenfritz, Carlos Augusto; Pekelmann Markus, Regina; Paz Hidalgo, Maria
Background: To date, no biomarker has been able to predict antidepressant response at an early blockade of norepinephrine or serotonin uptake. The transient nocturnal increase in plasma melatonin levels is upregulated by blocking these uptakes. The aim of this study was to test whether fluoxetine increase in urinary 6-sulfatoxymelatonin (aMT6s) is an indicator of serotonin uptake blockade. Methods: A total of 20 women (35–45 years of age) recruited from the community had a diagnosis of major depressive disorder confirmed by the Structured Clinical Interview for DSM-IV. Depressive symptoms were evaluated by the Beck Depression Inventory (BDI). Participants were instructed to take 20 mg of fluoxetine every morning. Every 4 weeks, the dose could be increased by 20 mg until symptom remission. The concentration of aMT6s was evaluated in overnight urine samples collected 1 day before and 1 day after the first fluoxetine dose. Results: An increase in aMT6s correlated to a decrease in BDI score evaluated on day 45 (ρ = −0.67, p = 0.024) was observed. Conclusions: Nocturnal increase in urinary aMT6s after the first day of medication use links the early mechanism of action of fluoxetine to its clinical output 45 days later. Thus, the relationship between urinary aMT6s excretion 1 day before/1 day after is a biomarker for predicting clinical output earlier, reducing illness burden and health care costs.